1992
DOI: 10.1007/bf00993226
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salicylic acid on growth and stomatal movements ofVicia faba L.: Evidence for salicylic acid metabolization

Abstract: The influence of salicylic acid on the growth and stomatal movements ofVicia faba L. was investigated. Whereas shoot length, fresh weight, and transpiration rates, which are directly correlated with stomatal pore widths, were only affected at salicylic acid concentrations higher than 3.5 mM after long-term treatments, guard cells in epidermal peels exhibited a high sensitivity at concentrations as low as 0.001 mM, resulting in stomatal closing. HPLC analysis of methanolic extracts from roots and leaves reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(54 citation statements)
references
References 29 publications
5
46
1
Order By: Relevance
“…Similarly, stomata in SA-deficient Arabidopsis nahG (27) or eds16 (115) plants do not respond to PAMPs (77). The defect in PAMP/bacterium-triggered stomatal closure in SA-deficient plants is interesting, as previous studies have shown that SA is a potent inducer of stomatal closure (66,75,83). Taken together, these results suggest mechanistic connections between PAMP signaling, SA homeostasis, and ABA homeostasis and signaling in guard cell response to bacteria.…”
Section: Signaling Components During Stomatal Response To Bacteria Ansupporting
confidence: 50%
“…Similarly, stomata in SA-deficient Arabidopsis nahG (27) or eds16 (115) plants do not respond to PAMPs (77). The defect in PAMP/bacterium-triggered stomatal closure in SA-deficient plants is interesting, as previous studies have shown that SA is a potent inducer of stomatal closure (66,75,83). Taken together, these results suggest mechanistic connections between PAMP signaling, SA homeostasis, and ABA homeostasis and signaling in guard cell response to bacteria.…”
Section: Signaling Components During Stomatal Response To Bacteria Ansupporting
confidence: 50%
“…Concentrations above 0.01 mM of MJ were reported to inhibit root growth in some species (Lois et al 1989). Treatment with 5 mM SA showed a 25 % reduction in the growth of Vicia faba L. after 7-day incubation (Manthe et al 1992). Exogenously applied SA has been shown to affect a variety of processes in plants, including stomatal closure, seed germination, fruit yield, and glycolysis (Klessig and Malamy 1994).…”
Section: Accumulation Of Bilobalide and Ginkgolides In G Biloba Cellmentioning
confidence: 99%
“…Interestingly, rapid closure of stomata and an increase in foliar H 2 O 2 have been shown to occur upon SA treatment of leaves (Manthe et al, 1992;Chen et al, 1993;Rao et al, 1997;Shirasu et al, 1997;Lee, 1998;Mori et al, 2001). This may be associated with SA-dependent inhibition of CAT activity (Sanchez-Casas and Klessig, 1994;Conrath et al, 1995;Durner and Klessig, 1996;Chen et al, 1997).…”
Section: Cat1 Activity Is Reduced In Lsd1mentioning
confidence: 99%